The Influence Of The Teacher's Work Environment On Teacher Performance At Citra Berkat Elementary School, Surabaya - Rumiyati Rumiyati; Silvianti Hia (Sekolah Tinggi Teologi Injili Indonesia Surabaya, 2022)
The purpose of the research is to address a series of “why do you want to do research and what do you want to get” questions. Research can be distinguished as follows: exploratory is research that aims to find new knowledge that has never existed. Verification is research that aims to test an existing theory. So that the discovery of a research result that can invalidate or strengthen existing knowledge or theory. Development is research that aims to develop existing research. Therefore, in this scientific paper, the author has a goal, namely: First, to find out how much influence the work environment has on teacher performance.